PKM Pemerdayaan Masyarakat Melalui Peningkatan Kapasitas Manajemen bagi Kelompok Pengerajin Uang Kepeng Kamasan Bali - Cokorda Krisna Yudha; Ida Bagus Gede Indra Wedana Purba; Bayu Pasupati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service program aims to increase partners' understanding and ability to prepare financial reports, taxation, and marketing strategies in the digital era. The method of implementing the service program was to carry out counseling. The implementation of activities was divided into six stages: situation analysis, formulating problems, proposing several solutions, designing programs, implementing programs, evaluating program results, and reporting. The partner of this program was the owner and craftsman of the kepeng money at UD Kamasan Bali. The instruments of this program were questionnaires and interviews. The service activity results showed that (1) there was an increased understanding of preparing financial statements based on SAK EMKM, (2) partners complied with applicable tax rules and could report Individual Taxpayers' Period and Annual Tax Returns (SPT), and (3) partners could use digital media properly and maximize the use of product e-catalogs.